Facilitating Ukrainian Refugees’ Continued Participation in Clinical Trials - Bloswick, Agata; Mustra, David; Harasymiv, Oksana; Dubov, Alex (The Hastings Center report, 2022)
Russia's invasion of Ukraine and the ongoing armed conflict are having a hugely damaging effect on health services and the health infrastructure in Ukraine. Hundreds of clinical trials have been halted, leaving patients without access to treatment and jeopardizing the development of promising new drugs. There is a lack of clarity on dealing with protocol deviations and other disruptions caused by war. This article proposes guidance on facilitating Ukrainian refugees’ continuation in clinical trials. The safety of study participants should be the main priority and guide every decision, regardless of any potential consequences for an ongoing trial. This commentary outlines policy recommendations regarding participants’ reenrollment, the handover of participants and data to new principal investigators, and the consent process as well as the sponsor's obligations related to translation, data transfer, and support for Ukrainian investigators. To ensure data integrity, investigators should carry out risk assessments of the further use of refugees’ data.